Preparation of metal sulfide flocculating constituent material and application of metal sulfide flocculating constituent material in strontium ion adsorption
By combining metal sulfide particles with cationic flocculant CPAM, the metal sulfide flocculatorum material is prepared, the problem of sinking and adsorption performance of composite materials in practical applications, and realizing good SR2+adsorption and good settlement performance.
Patent Information
- Application Number
- CN202411685612.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-23
- Publication Date
- 2025-01-24
AI Technical Summary
In actual applications, existing metal sulfide composite materials have problems of reduced adsorption rate and reduced adsorption capacity, and it is difficult to take into account both the sedimentation performance and the efficient Sr2+ removal performance.
By using cationic flocculants such as CPAM, metal sulfide particles are removed stabilized, and large -sized floc particles are condensed to prepare metal sulfide flocculant materials to improve their settlement performance and adsorption performance.
The good settling performance and excellent Sr2+ adsorption performance of the metal sulfide material are achieved, and the problems of difficult material settling and reduced adsorption performance in the existing technology are solved.
Smart Images

Figure CN119349734A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of radioactive wastewater treatment, and specifically relates to the preparation of a metal sulfide flocculant material and its application in the adsorption and removal of Sr from radioactive wastewater. 2+ Application in this area. Background Art
[0002] As a clean energy, nuclear power has broad application prospects. However, nuclear leakage and radioactive wastewater discharge caused by nuclear energy development have caused serious and irreversible harm to the environment and human health. 90 Sr is a fission product of nuclear fuel with a half-life of up to 29 years and strong mobility. Once it enters the human body, it will increase the incidence of bone cancer, seriously endanger human health, and cause serious pollution to the environment. Therefore, from the perspective of nuclear power development and human health, it is urgent to remove radioactive strontium. At present, there are many methods for removing radioactive strontium from water at home and abroad, such as chemical precipitation, evaporation concentration, membrane separation, adsorption, etc. Among these methods, adsorption is widely used due to its small amount of chemical reagents, simple operation, strong selectivity, and green environmental protection.
[0003] Metal sulfides have the characteristics of high adsorption capacity, fast adsorption speed, strong selectivity, wide applicable pH range, acid and alkali resistance and radiation resistance, and are a new generation of adsorption materials for efficient treatment of radioactive wastewater. Metal sulfides are mostly adsorption materials in powder form. Their sedimentation rate when dispersed in water is slow. It is difficult to achieve solid-liquid separation after adsorption. It requires the help of subsequent treatment processes such as membrane separation and centrifugation, which limits industrial application. The preparation of composite materials using metal sulfides as active substances and porous materials as carriers can effectively break through the bottleneck of metal sulfide powder in practical applications. At present, KMS-1 / PAN granular composite materials (RSC Advances, 2015, 5(111): 91431-91435) and PVDF / KCTS composite microspheres (Journal of Cleaner Production, 2023, 391: 136212) have been reported. These composite materials all support metal sulfide powder materials through carriers to aggregate into larger particles. However, the dense surface of these composite materials prevents ions from diffusing from the solution into the material, resulting in a significant decrease in the adsorption rate. At the same time, the composite materials block the adsorption sites of metal sulfides, weakening the adsorption performance of the material itself, such as a significant decrease in adsorption capacity. Therefore, when developing metal sulfide composite materials, how to balance the practical application characteristics of the composite materials and the high efficiency of Sr removal is a key issue. 2+ Performance is an issue that needs to be addressed urgently. Summary of the invention
[0004] The object of the present invention is to provide a metal sulfide flocculant material and a preparation method thereof. The material has good sedimentation performance and is therefore easy to use in practice. It also has excellent Sr 2+ The adsorption performance is expected to solve the shortcomings of the existing technology.
[0005] To achieve the above object, the present invention adopts the following technical solution: One of the purposes of the present invention is to protect a metal sulfide flocculant material, which utilizes the flocculation effect of a cationic flocculant to destabilize and aggregate metal sulfide particles into large-sized flocculent particles.
[0006] Furthermore, the particle size of the material is 0.11-600 μm.
[0007] Furthermore, the cationic flocculant is selected from at least one of polyaluminium chloride (PAC), cationic polyacrylamide (CPAM), FeSO4 and FeCl3, preferably CPAM. CPAM has a long-chain molecular structure, a high molecular weight, and a large number of active groups such as amide and carboxyl groups. Its active groups can adsorb and link with particles in the water to form a large flocculant with a porous structure and a certain mechanical strength. The larger size of the flocculant is beneficial to the sedimentation, clarification, filtration, centrifugation and other links in the water treatment process.
[0008] Furthermore, the metal sulfide particles are composed of an anion skeleton and ion-exchangeable cations; the anion skeleton is a negatively charged layered structure formed by Zn, Sn, and S elements connected by covalent bonds, and the ion-exchangeable cations are K + Or Na + , preferably K / Zn / Sn / S metal sulfide (KZTS-NS). K between the metal sulfide layers of KZTS-NS + Can be used with Sr 2+ Ion exchange occurs, thereby achieving efficient capture of Sr from wastewater 2+ However, KZTS-NS powder itself has problems such as difficult solid-liquid separation and practical application in practical applications.
[0009] Specifically, the present invention provides a KZTS-NS@CPAM flocculant material prepared by using CPAM as a K / Zn / Sn / S metal sulfide carrier, which can solve the disadvantage of difficult solid-liquid separation when the metal sulfide material is used alone to remove radioactive nuclides in water, and overcome the disadvantage of poor removal effect when using CPAM alone, thereby obtaining a metal sulfide flocculant material with excellent adsorption and sedimentation properties.
[0010] The second object of the present invention is to protect the preparation method of the metal sulfide flocculant material, which comprises firstly dispersing the metal sulfide particles in water by ultrasonic means to form a metal sulfide suspension, then adding a flocculant mother liquor into the metal sulfide suspension, stirring, settling, washing and freeze-drying, thereby obtaining the metal sulfide flocculant material.
[0011] Furthermore, the ultrasonic dispersion time is 0 to 60 min, preferably 30 min.
[0012] Furthermore, the concentration of the metal sulfide suspension is 0.4-1 g / L, preferably 1 g / L.
[0013] Furthermore, the concentration of the flocculant mother solution is 1-10 g / L, preferably 10 g / L.
[0014] Furthermore, the amount of flocculant mother solution added is 0.5-20 mL per 50-500 mL of metal sulfide suspension, preferably 10 mL per 500 mL.
[0015] Furthermore, the stirring speed is 100-200 rpm, preferably 200 rpm; the stirring time is 5-30 min, preferably 20 min.
[0016] Furthermore, the sedimentation time is 1 to 120 min.
[0017] Furthermore, the washing is performed using ultrapure water.
[0018] The third object of the present invention is to protect the metal sulfide flocculent material in the adsorption treatment of Sr in radioactive wastewater. 2+ Application in this area.
[0019] Furthermore, the application method is to mix the metal sulfide flocculant material with a Sr-containing 2+ The metal sulfide flocculant material can capture Sr in the wastewater. 2+ .
[0020] Optionally, the contact time is 1 to 12 h.
[0021] Optionally, the radioactive wastewater contains Sr 2+ The concentration is 5~100 mg / L.
[0022] Optionally, the pH of the radioactive wastewater may be 1 to 13. The metal sulfide flocculant material can maintain stable performance within a pH range of 2-13.
[0023] Optionally, the radioactive wastewater may include the following coexisting ions: K + 、Na + , Ca 2+ Mg 2+ The metal sulfide flocculant material has a great influence on Sr 2+ The removal of K + and Na + The ion effect is small.
[0024] After the metal sulfide flocculant material comes into contact with radioactive wastewater, it can reach adsorption equilibrium within 40 minutes, and its adsorption of Sr 2+ The adsorption capacity is not less than 40.04 mg / g.
[0025] The beneficial effects of the present invention are (1) The present invention is the first to use a cationic flocculant as a carrier of metal sulfide to prepare metal sulfide flocs, which can significantly improve the sedimentation performance of metal sulfides while retaining the adsorption performance of metal sulfides to the greatest extent.
[0026] (2) The flocculant material provided by the present invention has mild synthesis conditions, a simple preparation method, and the raw materials are cheap and readily available, with low cost.
[0027] (3) The solution of the present invention can solve the problem of small particle size of metal sulfide powder material and difficulty in solid-liquid separation, and overcome the disadvantage that most carrier composite metal sulfide processes will lead to a decrease in the adsorption performance of metal sulfide.
[0028] (4) The flocculent material prepared by the present invention has a large particle size, a certain mechanical strength, and is easy to settle in aqueous solution; 2+ Adsorption experiments (including kinetics, isotherms, acid and alkali resistance, the influence of coexisting ions, adsorption under different water backgrounds, etc.) confirmed that the prepared flocculent material can efficiently adsorb Sr 2+ , which has broad application prospects in the field of radioactive wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Stereoscopic microscope photograph (a), particle size distribution diagram (b) and SEM images (cd) of the KZTS-NS@CPAM flocculent material prepared in Example 1.
[0030] Figure 2 Removal of Sr from the KZTS-NS@CPAM flocculant material prepared in Example 1 2+ Kinetic curve diagram.
[0031] Figure 3 Removal of Sr from the KZTS-NS@CPAM flocculant material prepared in Example 1 2+Adsorption isotherm curve.
[0032] Figure 4 The KZTS-NS@CPAM flocculant material prepared in Example 1 has an initial pH range of 1 to 13 for Sr 2+ Removal effect diagram.
[0033] Figure 5 For different concentrations of K + 、Na + , Ca 2+ Mg 2+ Under the coexistence of Sr 2+ Removal effect diagram.
[0034] Figure 6 The KZTS-NS@CPAM flocculant material prepared in Example 1 was used to analyze the Sr concentration in ultrapure water, mineral water, tap water, lake water and sea water. 2+ Removal effect diagram. DETAILED DESCRIPTION
[0035] A metal sulfide flocculant material is provided with cationic polyacrylamide (CPAM) as a flocculant and K / Zn / Sn / S (KZTS-NS) as a metal sulfide. The KZTS-NS is first dispersed in water, ultrasonicated for 0-60 min to form a 0.4-1 g / L KZTS-NS suspension, then 50-500 mL of the KZTS-NS suspension is taken, 0.5-20 mL of CPAM mother liquor with a concentration of 1-10 g / L is added, the mixture is stirred at 100-200 rpm for 5-30 min, settled for 1-120 min, washed with ultrapure water, and freeze-dried to obtain a KZTS-NS@CPAM flocculant material.
[0036] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0037] Unless otherwise specified, the raw materials in this example were purchased from commercial sources.
[0038] The analysis method involved in this embodiment is as follows: Stereomicroscope photos were taken with a stereomicroscope (M165FC, Leica, Germany).
[0039] The particle size distribution was determined using a fully automatic laser particle size analyzer (ST-1076, Xiamen Easy Instrument Co., Ltd.).
[0040] SEM images were taken with a scanning electron microscope (Hitachi S-4800, Hitachi, Japan).
[0041] The metal ion concentrations were determined by inductively coupled plasma optical emission spectroscopy (ICP-OES, PerkinElmer Inc.).
[0042] Turbidity was measured using a turbidity meter (WZB-175, Shanghai Yidian Scientific Instrument Co., Ltd.).
[0043] In this embodiment, the removal rate and the decontamination factor are calculated by the following formula: R =( C 0 −C e ) / C 0×100% (1), DF = C 0 / C e (2), In the formula, C 0 and C e Represents Sr 2+ The initial concentration and equilibrium concentration of the solution, in mg / L.
[0044] Example 1 Preparation of KZTS-NS@CPAM flocculent material (1) K2CO3 (24 mmol), Zn powder (12 mmol), Sn powder (24 mmol), and S powder (120 mmol) were placed in a 100 mL polytetrafluoroethylene liner, 30 mL of ultrapure water was added and mixed evenly, and the reactor was placed at 200 °C for 4 d. The obtained product was washed several times with ultrapure water, CS2, and C2H5OH, and vacuum dried at 80 °C for 16 h. Finally, it was ground through a 100-mesh sieve to obtain brown-yellow powder KZTS-NS (Chemical Engineering Journal, 2020, 391: 123486).
[0045] (2) 0.5 g KZTS-NS and 0.5 L ultrapure water were added to a 1 L beaker to prepare a KZTS-NS suspension, which was then ultrasonically treated for 30 min. While the suspension was stirred at 200 r / min on a mechanical stirrer, 5 mL of 10 g / L CPAM mother solution was added. After stirring for 20 min, the product quickly settled to the bottom of the beaker. The supernatant was discarded and the product was washed with ultrapure water for several times. The product was freeze-dried for 48 h to obtain the KZTS-NS@CPAM flocculant material ( Figure 1 (a).
[0046] The particle size of the KZTS-NS@CPAM flocculant material prepared in this example was measured by a particle size analyzer, and the average particle size was found to be 182.89 μm ( Figure 1 b). It can be seen that compared with the original metal sulfide powder material, the size of the flocculent material has been greatly improved, which can improve the sedimentation efficiency during water treatment. At the same time, the SEM image of the KZTS-NS@CPAM flocculent material ( Figure 1 As can be seen from (cd) in the figure, there are stacked nanosheets attached to the surface of the flocculent material.
[0047] Example 2 Preparation of KZTS-NS@PAC flocculent material After preliminary optimization, 12.5 mL of PAC mother solution with a concentration of 1 g / L was added to the suspension in step (2), and the other operations were the same as those in Example 1 to obtain KZTS-NS@PAC flocculent material.
[0048] Example 3 KZTS-NS@Fe 2+ Preparation of flocculent materials After preliminary optimization, 7.5 mL of FeSO4 mother solution with a concentration of 10 g / L was added to the suspension in step (2), and the other operations were the same as in Example 1 to obtain KZTS-NS@Fe 2+ Flocculent material.
[0049] Example 4 KZTS-NS@Fe 3+ Preparation of flocculent materials After preliminary optimization, 2.5 mL of 10 g / L FeCl3 mother solution was added to the suspension in step (2), and the other operations were the same as in Example 1 to obtain KZTS-NS@Fe 3+ Flocculent material.
[0050] Application Example 1: Flocculent materials prepared with different flocculants capture Sr 2+ Ability test KZTS-NS and CPAM were mixed with KZTS-NS@CPAM, KZTS-NS@PAC, KZTS-NS@Fe 2+ and KZTS-NS@Fe 3+ The flocculants were mixed with 5 mg / L Sr 2+ The mixture was mixed with simulated radioactive wastewater (m (material mass): V (wastewater volume) = 1 g / L) and stirred at 25 °C for 2 h. After the reaction was completed, the suspension was taken and filtered with a 0.45 μm filter membrane. The Sr content in the filtrate was determined by ICP-OES. 2+ The concentration was measured and the turbidity of the supernatant was measured after 2 h of sedimentation. The results are shown in Table 1.
[0051] Table 1 Average particle size of different flocculants, turbidity of supernatant after 2 h of sedimentation, and adsorption of Sr for 2 h 2+ Decontamination factor
[0052] It can be seen from Table 1 that KZTS-NS@CPAM, KZTS-NS@PAC, KZTS-NS@Fe 2+ and KZTS-NS@Fe 3+ The average particle sizes of the flocculent materials were 182.89, 5.10, 7.62 and 6.15 μm, respectively. After 2 h of sedimentation, the KZTS-NS@CPAM, KZTS-NS@PAC, KZTS-NS@Fe 2+ and KZTS-NS@Fe 3+ The turbidity of the supernatant in the solution of the flocculant material was 10.5, 111.9, 46.5 and 28.1 NTU, respectively. This shows that the selection of different flocculants will affect the particle size of the composite material, and the larger the particle size, the more conducive to the sedimentation of the flocculants and the faster the sedimentation rate.
[0053] At the same time, CPAM alone can effectively inhibit the growth of Sr 2+ The removal effect is extremely low, and the apparent viscosity of the aqueous solution increases, which will cause secondary pollution to the wastewater. 2+ The decontamination factor is lower than that of KZTS-NS@CPAM flocs, indicating that the composite of KZTS-NS with CPAM as a carrier not only retains but also enhances the Sr removal of KZTS-NS to a certain extent. 2+ The enhancement may be due to: (1) the intercalation of CPAM molecular chains expands the interlayer space of KZTS-NS, allowing more hydrated Sr 2+ can enter the interlayer space and be captured; (2) the amide groups on CPAM increase the adsorption sites of the flocculants. Comparison of the four flocculant materials prepared using different flocculants shows that their adsorption of Sr 2+ The decontamination factors of the three flocculants were 52339.0, 51766.0, 17.0 and 16.1, respectively, indicating that different flocculants will enhance or weaken the adsorption capacity of metal sulfides. At the same time, although the adsorption performance of KZTS-NS can be enhanced by compounding KZTS-NS with PAC as a carrier, the sedimentation performance of the formed KZTS-NS@PAC floccules is not ideal, and the turbidity of the supernatant after 2 hours of sedimentation is as high as 111.9 NTU. This further shows that the KZTS-NS@CPAM flocculant material prepared using CPAM as a carrier has excellent sedimentation and adsorption properties.
[0054] Application Example 2: Capture of Sr by KZTS-NS@CPAM flocculent material2+ Kinetic testing The flocculent material prepared in Example 1 was mixed with 5 mg / L Sr 2+ The ion aqueous solution was mixed (m (material mass): V (solution volume) = 1 g / L), stirred at 25 °C, and a small amount of suspension was taken at regular intervals. After filtering with a 0.45 μm filter membrane, the Sr content in the filtrate was determined by ICP-OES. 2+ Concentration, the results are as follows Figure 2 shown.
[0055] Depend on Figure 2 It can be seen that the flocculant material has a significant effect on Sr 2+ The adsorption equilibrium can be reached within 40 min, and the adsorption speed is fast.
[0056] Application Example 3: Capture of Sr by KZTS-NS@CPAM flocculent material 2+ Adsorption isotherm test The flocculent material prepared in Example 1 was mixed with 5-100 mg / L Sr 2+ The ion-water solution was mixed (m (material mass): V (wastewater volume) = 1 g / L) and stirred at 25 °C for 12 h. After the reaction was completed, the suspension was taken and filtered with a 0.45 μm filter membrane. The Sr content in the filtrate was determined by ICP-OES. 2+ Concentration, the results are as follows Figure 3 As shown in Table 2.
[0057] The results show that the adsorption isotherm is more consistent with the Langmuir model, and the calculated adsorption of Sr by flocculants is 2+ The maximum adsorption capacity can reach 40.04 mg / g.
[0058] Table 2 Fitting data of different isothermal adsorption models
[0059] Application Example 4: Capture of Sr by KZTS-NS@CPAM flocculant material at different pH values 2+ Ability test The flocculent material prepared in Example 1 was mixed with Sr 2+ Ion-water mixture (m (material mass): V (solution volume) = 1 g / L, Sr in the mixture 2+ The concentration was 5 mg / L), and the mixture was stirred at 25 °C for 12 h. After the reaction was completed, the suspension was filtered with a 0.45 μm filter membrane and the Sr content in the filtrate was determined by ICP-OES. 2+ Concentration, the results are as follows Figure 4 shown.
[0060] Depend on Figure 4 It can be seen that the flocculent material can maintain the Sr 2+ High removal capacity, even at pH = 2 and 13, for Sr 2+ The removal rate is also above 79%.
[0061] Application Example 5 Coexisting Ions Capture Sr by KZTS-NS@CPAM Flocculent Material 2+ Impact test The flocculent material prepared in Example 1 was mixed with + 、Na + , Ca 2+ Mg 2+ Sr 2+ Ion-water mixture (m (material mass): V (solution volume) = 1 g / L, Sr in the mixture 2+ The concentration was 5 mg / L) and stirred at 25 °C for 12 h. After the reaction was completed, the suspension was filtered with a 0.45 μm filter membrane and the Sr content in the filtrate was determined by ICP-OES. 2+ Concentration, the results are as follows Figure 5 .
[0062] Depend on Figure 5 It can be seen that in the competitive K + and Na + Under the condition of excess ions, the flocculant material has a strong affinity for Sr 2+ The removal rate of Ca 2+ and Mg 2+ When the concentration of α is lower than 1 mmol / L, its presence has an effect on the flocculation material to Sr 2+ Therefore, the flocculent material can be used in the presence of a certain concentration of coexisting ions K + 、Na + , Ca 2+ Mg 2+ Effective adsorption of Sr in wastewater 2+ .
[0063] Application Example 6: KZTS-NS@CPAM flocculant material captures Sr in actual water background 2+ Test Tap water (TW), mineral water (MW), lake water (LW) and sea water (SW) were selected as actual water bodies, and Sr was added to them. 2+ To simulate the radiation exposure 2+ The actual water body polluted by adding Sr 2+Ultrapure water (UPW) was used as the control group (the mass concentration of the prepared water was 5 mg / L). Among them, ultrapure water was prepared by a laboratory water purifier; tap water was taken from the laboratory; mineral water was commercially available Nongfu Spring mineral water; lake water was taken from Furong Square of Minjiang College; and seawater was taken from Sansha Bay, Fuzhou City, Fujian Province. + 、Na + , Ca 2+ Mg 2+ The mass concentrations are summarized in Table 3.
[0064] Table 3 Water quality parameters of different water bodies
[0065] The flocculent material prepared in Example 1 was mixed with different actual water solutions (m (material mass): V (solution volume) = 1 g / L) and stirred at 25 °C for 12 h. After the reaction was completed, the suspension was taken and filtered with a 0.45 μm filter membrane. The Sr content in the filtrate was determined by ICP-OES. 2+ Concentration, the results are as follows Figure 6 .
[0066] Depend on Figure 6 It can be seen that the flocculant material has a significant effect on the Sr content in mineral water and tap water. 2+ The removal performance of Sr in lake water and sea water (>97.34%) is comparable to that in ultrapure water (99.90%). The removal effects in lake water and sea water decrease in turn, which may be due to the high content of coexisting cations in the water body affecting the removal of Sr by the flocculant material. 2+ Therefore, the flocculent material can adapt to the adsorption of Sr in daily water. 2+ removal.
[0067] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A metal sulfide flocculant material, characterized in that: The material utilizes the flocculation effect of a cationic flocculant to destabilize metal sulfide particles and aggregate them into large-sized floc particles.
2. The metal sulfide flocculant material according to claim 1, characterized in that: The particle size of the material is 0.11-600 μm.
3. The metal sulfide flocculant material according to claim 1, characterized in that: The cationic flocculant is selected from at least one of polyaluminium chloride, cationic polyacrylamide, FeSO4 and FeCl3.
4. The metal sulfide flocculant material according to claim 1, characterized in that: The metal sulfide particles are composed of an anion skeleton and ion-exchangeable cations; the anion skeleton is a negatively charged layered structure formed by covalently connecting Zn, Sn, and S elements, and the ion-exchangeable cations are K + Or Na + .
5. A method for preparing the metal sulfide flocculant material according to any one of claims 1 to 4, characterized in that: Firstly, metal sulfide particles are ultrasonically dispersed in water to form a metal sulfide suspension, and then a flocculant mother solution is added to the metal sulfide suspension, and the metal sulfide flocculent material is prepared through stirring, sedimentation, washing and freeze drying.
6. The metal sulfide flocculant material according to claim 5, characterized in that: The concentration of the metal sulfide suspension is 0.4-1 g / L.
7. The metal sulfide flocculant material according to claim 5, characterized in that: The concentration of the flocculant mother solution is 1-10 g / L, and the amount of the flocculant mother solution added is 0.5-20 mL per 50-500 mL of the metal sulfide suspension.
8. The metal sulfide flocculant material according to claim 5, characterized in that: The stirring speed is 50-200 rpm, and the time is 5-30 min; the sedimentation time is 1-120 min.
9. A metal sulfide flocculant material as claimed in any one of claims 1 to 4 for adsorption treatment of Sr in radioactive wastewater 2 + Application in this area.
Citation Information
Patent Citations
Preparation method of metal sulfide adsorbent for adsorbing radioactive strontium, metal sulfide adsorbent and water treatment method
CN108837794A
Composite adsorption material, preparation method thereof and application of composite adsorption material in uranium adsorption
CN117101613A
KR20240062578A